The Participation of the Arab Shami tribes in the liberation of Egypt - Al-Jiburi , Hashim Nawaf; Abbas , Abdul Hadi Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The liberation of Egypt on the hands of sham soldiers, which means that the tribes that participated in the Editing is in the highest degree in the tribes of the Sham, as well as the other tribes. Sham tribes from lakham , webble , bhraa, balkin ,ghassan, qadaeuh,and others with the battles of the liberation of egypt ,as these tribes were contributing to ther campaign that started from alsham countries to liberation egypt from byzantine occupation These tribes were under the leadership of amr ibn al –As (may God be pleased with you) it contributed prominently and effectively to the liberation of egyptian cities and fort and the expulsion of the byzantines from it.Therefore our study came under this constraint (the participation of the Arab Shami tribes with the liberation of Egypt).In order of to show the military role that played these tribes in the battles of Islamic liberation For Egypt.As for the conclusion of the research, it was the most prominent results that the study, in addition to the sources and references used in the research.